Revealing the Ritually Concealed: Custodians, Conservators, and the Concealed Shoe - Houlbrook, Ceri ca. 20./21. Jh. (Material religion, 2018)
Concealed shoes are footwear purposely concealed within domestic buildings. The motivations behind their concealments are unknown to us, but the prominent theory suggests that shoes were employed as apotropaic (evil-averting) devices. The metonymical connection between shoe and wearer is believed to imbue the shoe with the necessary protective power, and one theory suggests that, to possess this power, shoes must bear the unambiguous imprint of their past wearers, hence why the vast majority of them are old, well-worn or damaged. From the point of discovery (often during restructuring work), the concealed shoe's biography can follow a variety of courses. Some debate, for example, surrounds their removal. Some finders believe it to be bad luck to remove concealed shoes and therefore wish to keep them in situ. Others are donated to museums, where still more debate surrounds their treatment: should they be restored by textile conservationists or left in their original state, their damaged conditions being considered central to the interpretation of the custom? This paper aims to trace the complex biographies of several examples of concealed shoes following discovery, considering how they have been variously perceived and treated by their finders and custodians.